2016
DOI: 10.3748/wjg.v22.i36.8203
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of alpha-fetoprotein producing early gastric cancer with enteroblastic differentiation

Abstract: AIMTo investigate clinicopathological features of early stage gastric cancer with enteroblastic differentiation (GCED).METHODSWe retrospectively investigated data on 6 cases of early stage GCED and 186 cases of early stage conventional gastric cancer (CGC: well or moderately differentiated adenocarcinoma) who underwent endoscopic submucosal dissection or endoscopic mucosal resection from September 2011 to February 2015 in our hospital. GCED was defined as a tumor having a primitive intestine-like structure com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 25 publications
3
37
0
Order By: Relevance
“…Sarcomatoid and chordoid urothelial carcinoma were excluded after the identification of areas with classical YST pattern and immunohistochemistry results. Carcinoma with enteroblastic differentiation has been reported in several organs (gastrointestinal, lung, etc) [16], while carcinoma with hepatoid differentiation has been mainly reported in gynecologic tumors [17], and in urinary tract tumors already mentioned [4].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcomatoid and chordoid urothelial carcinoma were excluded after the identification of areas with classical YST pattern and immunohistochemistry results. Carcinoma with enteroblastic differentiation has been reported in several organs (gastrointestinal, lung, etc) [16], while carcinoma with hepatoid differentiation has been mainly reported in gynecologic tumors [17], and in urinary tract tumors already mentioned [4].…”
Section: Discussionmentioning
confidence: 99%
“…In case of stomach location, the gastric mucosal epithelium was covered with tubular adenocarcinoma, and the deeper part of the mucosal layer and the submucosa were composed of tubular adenocarcinoma and adenocarcinoma with enteroblastic differentiation [24]. Kinjo et al suggested that AFP-producing carcinoma developed from tubular adenocarcinoma and invaded into deeper layers [3].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of adenocarcinoma with enteroblastic differentiation cases have been reported to occur in the stomach . Compared with conventional gastric adenocarcinoma, gastric adenocarcinoma with enteroblastic differentiation shows aggressive behaviour characterised by frequent lymphovascular invasion, lymphatic and liver metastases, and is associated with a poor prognosis …”
Section: Introductionmentioning
confidence: 99%
“…The majority of adenocarcinoma with enteroblastic differentiation cases have been reported to occur in the stomach. 2,[12][13][14] Compared with conventional gastric adenocarcinoma, gastric adenocarcinoma with enteroblastic differentiation shows aggressive behaviour characterised by frequent lymphovascular invasion, lymphatic and liver metastases, and is associated with a poor prognosis. 2,12 Immunohistochemically, in addition to AFP, oncofetal proteins such as glypican-3 (GPC3) and spalt-like transcription factor 4 4 are reportedly associated with gastric adenocarcinoma with enteroblastic differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation